Association of Thyroid Hormones with Aggression: A Neuroendocrine Approach - Ramzan, Maryam; Masood, Muhammad Muzammil; Tahir, Muhammad; Pakeeza (Indus Journal of Bioscience Research, 2025)
Aggression, a hybrid behavior with biological, psychological, and social roots, is gradually associated with neuroendocrine mechanisms, particularly thyroid hormones. This review explains the complex association between thyroid hormones and aggressive behavior from clinical, neurodevelopmental, and neuroendocrine perspectives. Thyroid hormones, specifically triiodothyronine (T3) and thyroxine (T4), are critical in brain development, emotion regulation, and neurotransmitter intonation. Dysfunctions like hypothyroidism and hyperthyroidism are often associated with mood disturbances, irritability, impulsive behavior, and aggression. Moreover, the relationship between thyroid hormones and the hypothalamic-pituitary-adrenal (HPA) axis and their action on serotonergic, dopaminergic, and GABAergic systems makes them strong mediators for behavioral outcomes. Sex differences in thyroid dysregulation and aggression also specify the necessity for gender-specific research. Combining together clinical and experimental studies, this review highlights the aptitude of thyroid hormone profiling in risk assessment for aggression to the examination of thyroid-targeted treatments for the management of aggressive psychopathology.